TELAAH TERHADAP PRO DAN KONTRA HUKUMAN MATI DI INDONESIA DALAM PERSPEKTIF PIDANA ISLAM - Harahap, Risalan Basri (IAIN Padangsidimpuan, 2018)
Capital punishment is still carried out in many countries, including Indonesia. Considering that the death penalty involves human life, there are many pros and cons in the community. Each opinion group has put forward its statement according to the perspective they propose so that it becomes a prolonged legal polemic. however, the Indonesian government together with a number of elements of society that support the death penalty remain at the establishment, that capital punishment must still be carried out to protect life. This paper attempts to inform some of the death sentences that have been carried out for various specific crimes. This paper attempts to analyze how far the cases of execution can be justified according to Islamic criminal law. The results of this paper indicate that some of these crimes can indeed be subject to capital punishment, some still contain controversy, but some are actually released from the death penalty because the victim's family in the murder case has forgiven.